Diversi Terhadap Recidive Anak - Mita Dwijayanti (Trunojoyo Madura University, 2017)
AbstractSince the date of July 30, 2014 the Law No. 11 of 2012. One of the things that set new Law No. 11 of 2012 is Diversio. In the implementation, although Diversion is intended to protect children from stigmatization and pressure of the judicial process, but has not been fully implemented because of the Law No. 11 of 2012 are the terms and conditions of the diversion that one of them is the child who did the crime of repetition is not allowed to finish through the process of Diversion. Child in conflict with the law that could damage the system community, especially people of Indonesia and due to the mischief, a child has to deal with the law and go to prison children. Therefore, implementation of the concept of diversion is done with the intention to avoid children from the negative implications of the criminal justice system that is, avoiding the child will enter the criminal justice system and eliminate child labeled criminals against children who have already become victims